2011
DOI: 10.3762/bjoc.7.170
|View full text |Cite
|
Sign up to set email alerts
|

Access to pyrrolo-pyridines by gold-catalyzed hydroarylation of pyrroles tethered to terminal alkynes

Abstract: SummaryIn a simple procedure, the intramolecular hydroarylation of N-propargyl-pyrrole-2-carboxamides was accomplished with the aid of gold(III) catalysis. The reaction led to differently substituted pyrrolo[2,3-c]pyridine and pyrrolo[3,2-c]pyridine derivatives arising either from direct cyclization or from a formal rearrangement of the carboxamide group. Terminal alkynes are essential to achieve bicyclic pyrrolo-fused pyridinones by a 6-exo-dig process, while the presence of a phenyl group at the C–C triple b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…While terminal alkynes were reported to undergo 6-exo-dig cyclization to afford pyrrolopyridines, substrates with internal alkynes cyclized via a 7-endo-dig process to afford regioisomeric pyrroloazepines. [243] DFT calcu- lations correlated the change in regiochemistry to the relative electronic differences between the internal carbon in terminal and internal alkynes. Also, the 1,2-migration step was found to be crucial in determining the major/minor product selectivity.…”
Section: Selective Hydroarylation Of π-Systems By Furans Pyrroles and Thiophenesmentioning
confidence: 99%
See 1 more Smart Citation
“…While terminal alkynes were reported to undergo 6-exo-dig cyclization to afford pyrrolopyridines, substrates with internal alkynes cyclized via a 7-endo-dig process to afford regioisomeric pyrroloazepines. [243] DFT calcu- lations correlated the change in regiochemistry to the relative electronic differences between the internal carbon in terminal and internal alkynes. Also, the 1,2-migration step was found to be crucial in determining the major/minor product selectivity.…”
Section: Selective Hydroarylation Of π-Systems By Furans Pyrroles and Thiophenesmentioning
confidence: 99%
“…during the study of AuCl 3‐ catalyzed intramolecular hydroarylation of N‐propargyl‐pyrrole‐2‐carboxamides. While terminal alkynes were reported to undergo 6‐ exo ‐ dig cyclization to afford pyrrolopyridines, substrates with internal alkynes cyclized via a 7‐ endo ‐ dig process to afford regioisomeric pyrroloazepines [243] . DFT calculations correlated the change in regiochemistry to the relative electronic differences between the internal carbon in terminal and internal alkynes.…”
Section: Selective Hydroarylation Of π‐Systems By Furans Pyrroles and Thiophenesmentioning
confidence: 99%
“…More studies on the selectivity between direct cyclization product and cyclization‐rearrangement product revealed that less polar solvents favored the formation of 1,2‐migration products (Scheme 129). [149] …”
Section: Metamorphosis Of Heteroarene‐tethered Propargyl Amidesmentioning
confidence: 99%
“…[148] The Broggini group studied as imilar hydroarylation strategy of pyrroles tethered to terminal alkynes 513.I nterestingly, 5mol %A uCl 3 in refluxing CH 3 CN for 4hours resulted in the formation of pyrrolo-pyridines 514 through 6-exo-dig cyclization pathway indicating the pivotal role of the substitution on the alkyne terminus in directing the cyclization via 6-exo-dig or 7-endo-dig pathway.M ore studies on the selectivity between direct cyclization product and cyclization-rearrangementp roduct revealed that less polar solvents favored the formation of 1,2-migration products(Scheme 129). [149] Vander Eycken and co-workersa lso described intramolecular hydroarylation of pyrrole and indole-tethered alkynamides 520 under Au I -catalysis. In the first step, 4-component Ugi adduct of pyrrole or indole-2-carboxaldehyde with acid, propargylamine and isonitrile was synthesized.…”
Section: Metamorphosis Of Heteroarene-tethered Propargyl Amidesmentioning
confidence: 99%
“…10 in Scheme ) in addition to the rearranged product; the ratio of the two was dependent on the reaction temperature. , The formation of rearrangement products was rationalized via the intermediacy of the spiro fused derivative 12 derived from ipso addition to the pyrrole (Scheme ). The nonrearranged pyrroloazepinone skeleton was required in order to apply this chemistry to a total synthesis of stevensine or hymenin. Our preliminary work on Au-catalyzed hydroarylations , of imidazolyl alkynes with pyrroles showed that there was some substituent sensitivity in the reaction with respect to the fusion of the pyrrole ring .…”
mentioning
confidence: 99%